Evaluation of miRNA prediction tools and in silico analysis of micro and long non coding RNAs in sweet potato - Aswathy, M B (Department of Plant Biotechnology College of Agriculture, 2018)
The study entitled “Evaluation of miRNA prediction tools and in silico analysis of micro and long non coding RNAs in sweet potato (Ipomoea batatas L.)” was conducted at the ICAR-CTCRI, Sreekariyam. The objectives of the study is to compare different miRNA and target prediction tools and in silico analysis of the miRNAs and lncRNAs in sweet potato. The plant miRNA identification tools: NOVOMIR and miRPlant and miRNA-target prediction tools: psRNATarget and miRanda were compared. NOVOMIR and psRNATarget were found to be a better tool in miRNA identification and target prediction. MicroRNAs (miRNA) are 18-22nt small, endogenous non coding RNA that has prominent role in many biological processes. In the present study, we report the computational prediction of miRNAs and targets from expressed sequence tags (ESTs) of sweet potato. We predicted 13 novel potential miRNAs and 81 potential target genes and functionally characterized by BLASTX and BLAST2GO. The predicted target genes were credited with their role in signalling cascades, metabolism, and defence and stress responses. Another candidate that has more importance in the genome regulation is lncRNAs. lncRNAs are greater than 200 nucleotide length ncRNA candidate that holds functions at RNA level itself. RNAplonc is a plant long non coding RNA identification tool which uses 16 feature selection methods to predict long non coding RNA molecules. The present study which predicts 9215 lncRNAs and 8665 protein coding genes by RNAplonc in sweet potato for the first time using available ESTs sequences. Since there is a lack of lncRNA functional annotation tool, the functional analysis of predicted lncRNAs is quiet difficult. From the predicted miRNAs and lncRNAs two miRNAs and two lncRNAs were randomly selected for experimental validation by real time quantitative PCR using three different sweet potato varieties Sree Kanaka, ST13 and Khanjakad available at ICAR-CTCRI and compared the target gene’s expression in each variety. Validation results prove that both the miRNAs and lncRNAs shows their importance in crop improvement.